The Impact of Lifestyle Factors on the Development of Kidney Stones: Lifestyle Factors on the Kidney Stones Development - Ahmad, Nisar; Rehman, Ijaz Ur; Khan, Khalid; Javed, Mian Latif; Faisal, Mohammad; Naz, Rida (Pakistan Journal of Health Sciences, 2024)
Kidney stones are a common urological condition affecting millions worldwide, and lifestyle factors significantly influence their risk. Objectives: To assess the correlation between the risk of kidney stones and dietary habits, physical activity levels, hydration status, and body mass index in a cohort of 220 participants at Gomal Medical College, Dera Ismail Khan. Methods: A cross-sectional study was executed, with 220 adults stratified into two groups based on presence (n=111) or absence (n=109) of kidney stones. Validated structured questionnaires assessing hydration level, physical activity, body mass index, socioeconomic level, and dietary intake; animal protein, oxalates, and sodium were used to compile data. Chi-square testing and logistic regression allowed one to compute the odds ratios for kidney stone risk. Results: Significant risk factors for kidney stones were shown by high intake of animal protein (OR=3.88, p<0.001), high sodium intake (OR=1.98, p<0.05), and high oxalate intake (OR=1.65, p<0.05). High physical activity and adequate hydration were protective against kidney stones. A greater body mass index (OR=2.33, p<0.01) was linked to a higher risk. Socioeconomic level and stone frequency showed an association; the lower status was linked to a higher prevalence of stones (OR=1.75, p<0.05). Conclusions: It was concluded that the study underlined the strong relationships between particular lifestyle choices and kidney stone development probability. Good preventive measures are keeping an active lifestyle, making sure one is hydrated enough, and controlling their food. These findings highlight the importance of including lifestyle modifications in the clinical management of kidney stones.